2020
DOI: 10.3389/fpsyt.2020.00262
|View full text |Cite
|
Sign up to set email alerts
|

Using the Body When There Are No Words for Feelings: Alexithymia and Somatization in Self-Harming Adolescents

Abstract: The present case-control study aimed to investigate the relationship between alexithymia and somatic complaints in the psychopathological setting of non-suicidal self-injury (NSSI). A clinical sample of 134 adolescents (115 females; 85.5%) from 12 to 18 years old engaging in NSSI was compared with a control group of 243 high-school students (157 females; 64.6%) from 13 to 18 years old. Data were collected using two questionnaires: The Youth Self-Report 11-18 and the 20 Toronto Alexithymia Scale. In both cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 76 publications
(102 reference statements)
4
24
0
Order By: Relevance
“…In this field, clinicians and researchers from a psychodynamic perspective have considered risky behaviors (including nonfatal injuries) as an adolescent’s real attempt to cope with psychological discomfort [ 67 , 112 ]. Our findings provide further support to this evidence, suggesting that the recurrence of accidents may be considered a result of adolescents’ difficulties in managing their emotions and psychological sufferance [ 113 , 114 , 115 ]. At the same time, as suggested by Carbone [ 112 ], subsequent recurrent ED visits due to MVCs may be interpreted as an unconscious attempt to receive both psychical and psychological help from health operators.…”
Section: Discussionsupporting
confidence: 79%
“…In this field, clinicians and researchers from a psychodynamic perspective have considered risky behaviors (including nonfatal injuries) as an adolescent’s real attempt to cope with psychological discomfort [ 67 , 112 ]. Our findings provide further support to this evidence, suggesting that the recurrence of accidents may be considered a result of adolescents’ difficulties in managing their emotions and psychological sufferance [ 113 , 114 , 115 ]. At the same time, as suggested by Carbone [ 112 ], subsequent recurrent ED visits due to MVCs may be interpreted as an unconscious attempt to receive both psychical and psychological help from health operators.…”
Section: Discussionsupporting
confidence: 79%
“…Some studies have identified that somatic symptoms are linked with psychological or physiological abnormalities, which could indicate a pathological condition (14). Meanwhile, Raffagnato A et al reported that patients expressed their mental state through somatization symptoms (15). For example, approximately, 15%-45% of patients with persistent pain suffer from various degrees of anxiety (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Some published studies regarding adolescents have associated alexithymia with various psychopathological conditions [ 43 , 44 , 47 ], because it has been found to be related to an emotional dysregulation acquired already in infancy, and transmissible from one generation to the next [ 34 , 35 , 36 ]. The adolescents in the present study had a psychiatric diagnosis with which alexithymia may be associated.…”
Section: Discussionmentioning
confidence: 99%
“…The first binomial logistic regression was run to identify the dimension of alexithymia most impaired in socially-withdrawn adolescents. In fact, considering that the presence of alexithymic traits is a characteristic of different psychopathological disorders [ 43 , 44 , 47 ], we wanted to better investigate which specific aspect of alexithymia (i.e., difficulty in recognizing emotions, difficulty in expressing them, or concrete and externally-oriented thinking) was the most influential on social withdrawal. The presence or absence of social withdrawal (two levels) was input in the model as the dependent variable, with the three subscales of the TAS-20—difficulty describing feelings (DDF), difficulty identifying feelings (DIF) and externally-oriented thinking (EOT)—as predictors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation